Dietary Antigens Induce Germinal Center Responses in Peyer's Patches and Antigen-Specific IgA Production - Hara, Satoko; Sasaki, Takaharu; Satoh-Takayama, Naoko; Kanaya, Takashi; Kato, Tamotsu; Takikawa, Yui; Takahashi, Masumi; Tachibana, Naoko; Kim, Kwang Soon; Surh, Charles D.; Ohno, Hiroshi (Frontiers in Immunology, 2019)
The primary induction sites for intestinal IgA are the gut-associated lymphoid tissues (GALT), such as Peyer’s patches (PPs) and isolated lymphoid follicles (ILFs). The commensal microbiota is known to contribute to IgA production in the gut; however, the role of dietary antigens in IgA production is poorly understood. To understand the effect of dietary antigens on IgA production, post-weaning mice were maintained on an elemental diet without any large immunogenic molecules. We found that dietary antigens contribute to IgA production in PPs through induction of follicular helper T cells and germinal center B cells. The role of dietary antigens in the PP responses was further confirmed by adding bovine serum albumin (BSA) into the elemental diet. Although dietary antigens are important for PP responses, they have fewer effects than the microbiota on the development and maturation of ILFs. Furthermore, we demonstrated that dietary antigens are essential for a normal antigen-specific IgA response to Salmonella typhi serovar Typhimurium infection. These results provide new insights into the role of dietary antigens in the regulation of mucosal immune responses.